Sistem dan Etos Kerja Pengelolaan Limbah Medis RSUD Sawerigading Kota Palopo Perspektif Etika Lingkungan Ekosentrisme - Darussalam, Fajrul Ilmy; Indra, Andi Batara; Rahman, Saifur; Maharani, Maharani (Prodi Sosiologi FISIP Universitas Teuku Umar, 2024)
This research aims to analyze ecocentrism values in various medical waste management efforts of Sawerading Hospital. This research is a field research, using qualitative methods related to actual problems. This research prioritizes philosophical reflection efforts on a problem, with an environmental ethics study approach using the theory of ecocentrism. This research began with data collection, grouping primary and secondary data, systematizing research data, and analyzing the results. Data analysis uses methodical elements such as description, interpretation, internal coherence, and confirmability. The results of this study are 1) Sawerigading Hospital's medical waste management efforts include the existence of a person in charge of managing hospital waste, the availability of hospital waste management facilities and equipment, the existence of liquid and solid waste management in accordance with laws and regulations, and regulated liquid quality standards and all of which have been described in the system, mechanism, and standard operating procedures for medical waste management, 2) the principle of partnership, the principle of dynamic balance, and the principle of diversity are contained in the system and work ethic of medical waste management at RSUD Sawerigading, which is also in line with the value of awareness and togetherness, the value of benefits and sustainability, and the value of responsibility for waste management by the community as well as local governments in the public service of South Sulawesi Province.